1977
DOI: 10.1128/aac.12.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Stability of Cephalothin and Cefazolin in Buffer or Human Serum

Abstract: A marked loss in potency was observed when cephalothin was incubated for 5 h in human serum at 37°C. Cefazolin was stable under these conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…For instance, Qureshi et al (2013) reported that at 25°C, the CXM that remained in a deionized water solution was approximately 70% of the initial concentration after 30 h. However, the remaining proportion of CXM in the investigated CPWW eff was approximately 85% at 25°C after 30 h. The varied degradation rates of cephalosporins in different kinds of solutions have also been reported by other scholars (Glaria et al, 2003;Pitkin et al, 1977). This phenomenon could be explained by different ingredients in the solution, which might catalyze or inhibit the degradation of cephalosporins in different mediums.…”
Section: Effect Of Temperature On the Persistence Of Cephalosporins Isupporting
confidence: 61%
“…For instance, Qureshi et al (2013) reported that at 25°C, the CXM that remained in a deionized water solution was approximately 70% of the initial concentration after 30 h. However, the remaining proportion of CXM in the investigated CPWW eff was approximately 85% at 25°C after 30 h. The varied degradation rates of cephalosporins in different kinds of solutions have also been reported by other scholars (Glaria et al, 2003;Pitkin et al, 1977). This phenomenon could be explained by different ingredients in the solution, which might catalyze or inhibit the degradation of cephalosporins in different mediums.…”
Section: Effect Of Temperature On the Persistence Of Cephalosporins Isupporting
confidence: 61%
“…All urine samples were frozen until analyzed. Although cefazolin is more stable than other cephalosporins, 14 care was taken to chill samples immediately on collection. Serum was centrifuged and then frozen until analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…All urine samples were frozen until analysis. Since cephalothin quickly loses activity at body and room temperatures, 17 care was taken to chill samples immediately on collection. Serum was centrifuged and then frozen until analysis.…”
Section: Methodsmentioning
confidence: 99%